Calcium release-mediated adsorption and lubrication of salivary proteins on resin-based dental composites. (November 2022) - Tang, Yue; Lei, Lei; Yang, Dan; Zheng, Jing; Zeng, Qihang; Xiao, Heng; Zhou, Zhongrong
Abstract: The lack of wear resistance is always a challenge for clinical applications of resin-based dental composites (RBDCs). In this study, the role of the calcium release from RBDCs in the adsorption and lubrication of salivary proteins was investigated, aiming to provide useful insights concerning the development of high-performance RBDCs. Three experimental RBDCs with distinct calcium-releasing capabilities were prepared using calcium phosphate particles as inorganic fillers. Salivary protein adsorption and film-forming on RBDC surfaces were characterized by atomic force microscopy, while the mechanical properties and lubricating effect of salivary pellicle were examined using nano-indentation/scratch techniques. Results showed that calcium release from RBDCs plays a crucial role in mediating the electrostatic interaction between salivary proteins and composite surface, thereby promoting the formation of salivary pellicle with a multi-layer structure. The mechanical properties and lubricating effect of the pellicle are positively related to the level of calcium release. In sum, for RBDCs with robust calcium release, saliva provides effective lubrication to resist composite wear. Incorporating calcium compounds is a promising way to improve the wear resistance of RBDCs in the oral cavity. Graphical abstract: Image 1 Highlights: Calcium release from RBDCs aids the adsorption and lubrication of salivary proteins. Greater lubricating effect occurs on the RBDCs of higher calcium release. Robust calcium release mediates electrostatic interaction between proteins and RBDCs. Incorporating calcium compounds is a promising way to improve RBDCs wear resistance.